Supervisory Control for High-Voltage Direct Current Transmission Systems 1. Issue 1 (July 2017) - Rodríguez, Miguel Romero; Delpoux, Romain; Piétrac, Laurent; Dai, Jing; Benchaib, Abdelkrim; Niel, Eric
Abstract: The growth of renewable energy production is changing the future of power transmission systems. In recent years, High-Voltage Direct Current (HVDC) technologies based on Modular Multilevel Converters (MMC) are embraced by industry and academia as a solution for the efficient integration of renewable energies into electrical grids. Faster and more complex control strategies will be needed in this domain which nowadays relies heavily on human decision. This paper proposes a Discrete Event System (DES) approach to manage the control responses to deploy in an HVDC grid. Based on Discrete Event Systems (DES) modelling and Supervisory Control Theory (SCT), this paper proposes a method for synthesizing a supervisory control for HVDC systems, which focuses on local observations and limits the number of events to be communicated. The method is validated by simulation for the start-up of a point-to-point link.